Comparative Study Between NBC 105:2020 and IS 1893:2016 (Part 1) in torsionally irregular structure - Chaudhary, Hikmat Bahadur (Journal of NAST College, 2025)
Nepal lies in seismically vulnerable zone. Nepal has been hit by major earthquakes since long time, among them earthquake of 1990, 2015 AD, Jajarkot earthquake are prominent and destructive earthquakes in Nepal. In these above listed earthquakes Nepal has suffered huge loss of property and life. To minimize the losses Nepal has developed and implemented its own code NBC 105:1993 till 2019. Since Nepal lie in Indian sub-continent and NBC 105:1993 did not get updated, hence Nepal has been using IS 1893:2002 and IS 1893:2016 widely. After the NBC 105 was updated in 2020 there were major changes in the code. The major changes seen in the code are 4 types of soil type was introduced, seismic zoning was done different than IS code. The serviceability criteria are also introduced in the code. So, this article studies about comparative study between the codes in different soil types in torsionally irregular structure. The value of base shear is less by 40.57%, 18.52% and 43.32% from IS code with respect to NBC Code in hard soil, medium soil and soft soil respectively. The value of storey drift in X direction is less than 38.95%, 14.63% and 40.60 % from IS code with respect to NBC Code in hard soil, medium soil and soft soil respectively. The value of storey drift in Y direction is less than 40.92%, 16.64% and 42.01% from IS code with respect to NBC Code in hard soil, medium soil and soft soil respectively. Hence due to adaptation of latest seismic index result in higher lateral forces in the torsionally irregular structures in NBC 105:2020.